Identification of putative new tomato allergens and differential interaction with IgEs of tomato allergic subjects - Welter, S.; Lehmann, K.; Dölle, S.; Schwarz, D.; Weckwerth, W.; Scheler, C.; Worm, M.; Franken, P. (Clinical and experimental allergy, 2013)
Summary Background Tomato became one of the world‐wide most consumed vegetables, unfortunately accompanied by an increasing risk of tomato allergy affecting certain people. As tomato allergic subjects show highly variable reactions in clinical allergy tests, it is difficult to identify cultivars or differentially treated tomato plants where a significant reduction in the allergenic potential over all subjects of a cohort can be detected. Objective This study was carried out to test the hypothesis that individual variability is based on differential reactions of single subjects to particular allergens in tomato fruits of plants with certain genetic background or cultivated under distinct conditions. Methods Proteins were extracted from tomato fruits of the previously investigated genotypes 76R, its mycorrhizal mutant RMC, and the cultivar Counter, fertilized with different forms of nitrogen in deficit or excess. 2‐D immunoblots were carried out with sera of nine tomato allergic subjects, beforehand analysed in skin prick tests. Results In total, ten putative tomato allergens were identified in these immunoblots. No correlation was detected between individual skin prick test results and the quantity of positive reactions to putative allergens. IgEs of each subject showed reactions to nearly every identified putative allergen, but reactions were dependent on genotype and growth conditions. Among the ten putative tomato allergens, five new candidates were identified as follows: an endo‐β‐mannanase, a pectinacetylesterase, a pectinesterase inhibitor, an aspartyl protease family protein and a protein of unknown function. Conclusion and Clinical Relevance The hypothesis that high interindividual differences in allergic reactions are based on the interactions between the IgEs of allergic subjects with particular allergens has to be rejected. However, five proteins with putative clinical relevance as tomato allergens could be newly identified.